PENGARUH SUBTITUSI BUBUR LABU KUNING (Cucurbita moschata) TERHADAP KUALITAS BAKSO AYAM - Herwwin V. Manurung; Lucia C. Mandey; Thelma D.J. Tuju; Maya M. Ludong (COCOS, 2015)
ABSTRACTThis study aims to determine the formula pulp pumpkin and chicken, to get the quality of meatballs quality obtain and evaluate the level of preference panel which includes flavor, aroma, texture, color, appearance of the mix of chicken meatballsproduct and pumpkin. Benefits studies provide information about the quality of chicken meat balls with the addition of pumpkin pulp and introduce such products as diversification nutrient-rich food. This study uses a completely randomized design (CRD), which consists of treatment A = 20% pureed pumpkin mixture and 80% chicken meat, B = 30% pureed pumpkin mixture and chicken meat 70%, C = 40% mixture of pumpkin pulp and 60% chicken, D = 50% mixture of pumpkin pulp and 50% of chicken meat. This study suggests that chicken meatballs with pumpkin pulp mixture of 20% and 80% of chicken meat based on organoleptic test are the most favored treatment by the panelists in terms of aroma and flavor, while in terms of texture on the pumpkin pulp mixture of 30% and chicken 70%, and the color of the pumpkin pulp mixture of 50% and 50% of chicken meat. The chemical testing panelists preferred treatment is the addition of pumpkin pulp 20% and 80% of chicken meat with the following results: 72.29% moisture content, ash content of 1.63%, 1.63% fat content, protein content and carbohydrate 13:36% 11.62%.Keywords: pumpkin, porridge, chicken meatballs